Intranasal epinephrine in dogs: Pharmacokinetic and heart rate effects - Kenneth L. Dretchen; Zack Mesa; Matthew Robben; Desmond Slade; Scott Hill; Claire Croutch; Kyle Kappeler; Michael Mesa (Wiley, 2020)
Abstract Epinephrine is the standard of care for the treatment of severe allergy and anaphylaxis. Epinephrine is most often administered through the intramuscular (IM) route via autoinjector. The current study aimed to evaluate an alternative method of epinephrine treatment through intranasal (IN) delivery in dogs. The pharmacokinetic (PK) parameters of maximum plasma concentration (Cmax), time to reach maximum plasma concentration (Tmax), and area under the plasma concentration‐time curve from 0 to 90 minutes (AUC0-90) were observed after IN epinephrine (2, 3, 4, 5, 10, and 20 mg) and IM epinephrine via autoinjector (0.15 and 0.3 mg) for 90 minutes. Heart rate effects were measured after IN (2 and 5 mg) and IM (0.15 and 0.3 mg) epinephrine administration. IN epinephrine (5 mg) demonstrated significantly greater plasma epinephrine concentration at 1 minute as compared with IM epinephrine (0.3 mg) (1.68 ± 0.65 ng/mL vs 0.21 ± 0.08 ng/mL, P = .03). There were no significant differences in Cmax, Tmax, and AUC0-90 between 2‐mg IN and 0.15‐mg IM epinephrine or between 5‐mg IN and 0.3‐mg IM epinephrine. IN epinephrine reduced heart rate increases, as compared to IM epinephrine. IN and IM epinephrine were both well‐tolerated. Overall, IN epinephrine demonstrated advantages over IM epinephrine, including the rapid increase in plasma epinephrine and lack of increased heart rate over time.